ESMRMB 2025 focus topic: cycle of quality—from concept to clinical and scientific impact - Küstner, Thomas; Haast, Roy; Priovoulos, Nikos; Clement, Patricia; dos Santos, Daniel Pinto (Magma (New York, N.Y.), 2025)
Across the plenary and four educational sessions, the speakers explore how quality manifests at every stage of the MRI cycle: from acquisition and analysis, to algorithmic design, to harmonization, and ultimately, to research dissemination. [...]Bertrand Thirion (“AI and Harmonization: Standardization for robust algorithms?”) tackles the interaction between AI and harmonization, asking whether harmonization should precede AI modeling or be embedded within it. Understanding and mitigating confounding factors”) introduces the multifactorial nature of qMRI confounds—ranging from physiological noise and scanner instabilities to the specific choice of fitting models and parameters. Task-based evaluations, artifact quantification, and visual integrity scores as alternatives or supplements to traditional measures like signal-to-noise ratio (SNR) are presented.